Kajian Karakteristik Penderita Gagal Ginjal Kronis Dalam Terapi Hemodialisis - Cipto, Cipto; Siswoko, Siswoko; Normawati, Ajeng Titah; Uripno, Pambayun Sugeng (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Characteristics that greatly influence a person's lifestyle include chronic kidney failure sufferers undergoing hemodialysis therapy. Patients with chronic kidney failure experience a gradual decline in kidney function which is quite severe. This is caused by various diseases that are progressive and generally cannot be recovered. The aim of this research is to determine the picture of chronic kidney failure undergoing hemodialysis therapy. This research method is descriptive quantitative by explaining the distribution of frequencies and percentages. The sample in this study amounted to 30 people with the criteria being patients suffering from chronic kidney failure who underwent hemodialysis with compensatory awareness. The research was conducted at the Blora District Hospital by researchers in October 2023. The results of the study showed that the majority of kidney failure patients undergoing hemodialysis therapy were women, the age characteristics reached early old age or in the range of 45 to 55 years, the majority had a high school or equivalent education, and the average is a housewife. Most of the responders had undergone hemodialysis for more than two years. Based on these results, it can be a basis or suggestion for developing further studies to analyze the correlation of each characteristic with the phenomenon of symptoms that occur in hemodialysis patients.Keywords: chronic renal failure, hemodialysis, characteristics